ANALISIS KEBUTUHAN PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS GENIALLY PADA MATERI MEMBANDINGKAN BILANGAN PECAHAN KELAS V SD - Salsabila, Khairinnisa; Karlimah; Nuryadin, Asep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of utilization of creative and innovative learning media causes a low level of student understanding of subject matter, especially mathematics. This study aims to determine the needs of learning media on the material of comparing fractions in grade V elementary school. This research is part of development research using the ADDIE model, but at this initial stage it only focuses on the needs analysis stage. The research subjects consisted of 31 students and 1 fifth grade educator of SDN Sindanggalih. Data collection techniques were carried out using observation, interview, and questionnaire distribution methods. Based on the results of data analysis, it was found that both teachers and students need more interactive mathematics learning media that can attract learning interest. Therefore, it is necessary to develop Genially-based interactive multimedia as a solution that suits the needs of mathematics learning on the material of comparing fractions.